2017
DOI: 10.1007/s10865-017-9874-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between daily pain and affect in women with rheumatoid arthritis: lower optimism as a vulnerability factor

Abstract: The aim of the study was to examine the moderating effect of optimism on the relationship between daily pain-daily affect. Fifty-four female patients with rheumatoid arthritis completed self-report measures of optimism (once), daily pain and daily positive and negative affect for 7 consecutive days during hospitalization. Results of multilevel random coefficients modeling demonstrated a significant cross-level interaction for daily negative affect only. Simple slopes analysis revealed that low optimism was rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Deficiency of optimistic thinking may also be related to negative affect/distress, contributing to anxiety, depression, and hostility. 47,48 These findings suggest that different symptoms may share several common features such as vulnerable temperament and negative affectivity. Identification of modifiable transdiagnostic factors is critical to treat depressed patients with multiple comorbid symptoms.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Deficiency of optimistic thinking may also be related to negative affect/distress, contributing to anxiety, depression, and hostility. 47,48 These findings suggest that different symptoms may share several common features such as vulnerable temperament and negative affectivity. Identification of modifiable transdiagnostic factors is critical to treat depressed patients with multiple comorbid symptoms.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, depression, anxiety, and hostility were all connected to optimism. Deficiency of optimistic thinking may also be related to negative affect/distress, contributing to anxiety, depression, and hostility [ 47 , 48 ]. These findings suggest that different symptoms may share several common features such as vulnerable temperament and negative affectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Different points were used according to each patient's complaints. A total of 15 points were used for a respective absolute frequency of: frontal (4), B frontal (4), AB frontal (1), C frontal, E frontal (1), H frontal (1), I frontal (1); B dorsal (1), C Dorsal (1), E Dorsal (1), D side accessory (3), D1 side accessory (1), F accessory (1), multiple points in VB (1); and NA point (1). After the Pearson correlation analysis, it was possible to identify that the D1 side accessory and H frontal were the points with significant association (p<000,1) with the improvement of general well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Results suggest that pain and NA were more strongly related for individuals with greater average NA or depressive symptoms [45,50,53,58]. In one study, pain and NA were also more strongly related for individuals with more severe anxiety symptoms [45].…”
Section: Pain and Affect 15mentioning
confidence: 89%
“…Within individuals, pain was positively associated with NA variables across studies of mixed chronic pain [44,45], back pain [46,47], fibromyalgia [48][49][50], rheumatoid arthritis [51][52][53], osteoarthritis [54,55], mixed rheumatic disease [56][57][58], IBS [59], CRPS [60], and migraine [61]. Several studies also found pain to be negatively associated with PA in general chronic pain [44,62], fibromyalgia [48,49,63], rheumatoid arthritis [52,53,64,65], osteoarthritis [55,66], and mixed rheumatic disease [56,58]. Additionally, a higher ratio of PA to NA was associated with less pain in patients with osteoarthritis [55,67].…”
Section: Contemporaneousmentioning
confidence: 99%